Red Hook Road : a novel - Waldman, Ayelet. (Doubleday, 2010)
After John Tetherly and Becca Copaken die in a freak car accident an hour after their wedding, their families are left to bridge stark class and cultural divides, and eventually forge deep-rooted bonds thanks to the twin deities of love and music. Becca's family is well off, from New York, and summers in Red Hook, Maine, a small coastal town where John's blue-collar single mother, Jane, cleans houses for a living. They interact, awkwardly, over how to bury the couple, the staging of an anniversary party, and over Jane's adopted niece, whose amazing musical talent makes a connection to Becca's ailing grandfather, a virtuoso violinist, who agrees to give her lessons. Becca's younger sister, Ruthie, a Fulbright scholar, meanwhile, falls in love with John's younger brother, Matt, the first Tetherly to go to college, before he drops out to work at a boatyard and finish restoring his brother's sailboat, which he plans on sailing to the Caribbean.